2021
DOI: 10.1097/mlr.0000000000001525
|View full text |Cite
|
Sign up to set email alerts
|

Payment Discrepancies and Access to Primary Care Physicians for Dual-eligible Medicare-Medicaid Beneficiaries

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…31 Our study, along with others that have found limited impacts of the reimbursement bump on provider participation in Medicaid and use of other preventive care services highlight the importance of policy implementation, such as outreach efforts to increase providers' awareness of the policy and assistance for signing up for the program. 22,23,32 Moreover, it is possible that even with the reimbursement bump Medicaid vaccine administration reimbursements remained lower than those of commercial insurance plans. Most states did not increase vaccine administration reimbursements to Medicare rates and instead opted for lower VFC maximum rates.…”
Section: Discussionmentioning
confidence: 99%
“…31 Our study, along with others that have found limited impacts of the reimbursement bump on provider participation in Medicaid and use of other preventive care services highlight the importance of policy implementation, such as outreach efforts to increase providers' awareness of the policy and assistance for signing up for the program. 22,23,32 Moreover, it is possible that even with the reimbursement bump Medicaid vaccine administration reimbursements remained lower than those of commercial insurance plans. Most states did not increase vaccine administration reimbursements to Medicare rates and instead opted for lower VFC maximum rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, barriers exist that limit dually-enrolled patients from accessing primary care. Most states cap reimbursements for dually-enrolled patients at the Medicaid fee, disincentivizing providers from caring for these patients 9,10 . Socioeconomic constraints, such as a lack of available transportation or unaffordable copays, may also prevent dually-enrolled patients from accessing primary care 1,2 .…”
mentioning
confidence: 99%
“…Socioeconomic constraints, such as a lack of available transportation or unaffordable copays, may also prevent dually-enrolled patients from accessing primary care 1,2 . As a result, dually-enrolled patients may be disproportionately limited from receiving necessary primary care and chronic disease management, potentially contributing to disparities in hospitalizations 9–11 …”
mentioning
confidence: 99%